(untitled) (Web of Teachers: Inderscience Research, 2024)
Improving the pedagogical abilities of teachers of preschool education in higher educational institutions in an integrative direction is considered as a new social need to further increase the quality of higher education. This article talks about the importance of improving the pedagogical skills of teachers in an integrative direction in the educational process.